2019
DOI: 10.1109/access.2019.2922974
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study of Smartphone-Based Indoor Activity Recognition via Xgboost

Abstract: Recently, multi-floor indoor positioning has become increasingly interesting for researchers, in which accurate recognition of indoor activities is critical for the detection of floor changes and the improvement of positioning accuracy according to indoor landmarks. However, we have not found a comprehensive study for recognizing indoor activities related to multi-floor indoor positioning based on a robust machine learning algorithm. In this work, we propose a framework for recognizing five indoor activities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Y. Mishina, R. Murata, Y. Yamauchi, T. Yamashita, and H. Fujiyoshi claim that RF is more robust than other famous models and have been utilized in many fields such as, computer visions and pattern recognition [49]. The common weakness in using RF is the processing needs more time when applied to large amounts of data because it has to build many tree models [50]. A large number of trees also require significant memory capacity [49].…”
Section: ) Overview Of Machine Learning Techniquesmentioning
confidence: 99%
“…Y. Mishina, R. Murata, Y. Yamauchi, T. Yamashita, and H. Fujiyoshi claim that RF is more robust than other famous models and have been utilized in many fields such as, computer visions and pattern recognition [49]. The common weakness in using RF is the processing needs more time when applied to large amounts of data because it has to build many tree models [50]. A large number of trees also require significant memory capacity [49].…”
Section: ) Overview Of Machine Learning Techniquesmentioning
confidence: 99%
“…The paper concluded that their proposed XGBoost model outperformed the other classifiers. In a recent contribution, Zhang et al [33] have used barometer, gyroscope and accelerometer to record five movements of multi-floor indoor activities. The recorded movements were elevator taking, stair climbing, stillness, escalator taking and walking.…”
Section: Use Of Boosting Algorithms For Pacmentioning
confidence: 99%
“…Although some studies in Table 1 are providing high accuracy, all these differences make their performance incomparable. For example, Guo et al [32] used the XGboost classifier and achieved an f-measure score of 99%, while Zhang et al [33] have achieved f-measure of only 84.14% using the same classifier. Moreover, the impact of feature selection methods on the performance of boosting classifiers is not studied systematically considering the domain of PAC, and very little is known about how these classifiers behave when the feature selection stage is incorporated before classification.…”
Section: Limitations In Existing Boosting-based Pac Systemsmentioning
confidence: 99%
“…XGBoost algorithm is improved based on GBDT (Gradient Boosting Decision Tree) algorithm [26], which is a kind of supervision algorithm [27]. The idea is to establish a certain number of classification regression trees, so that the predicted number value of the tree group is as close to the real number value as possible and has the greatest generalization ability [28]. The advantage of XGBoost algorithm is that it is hard to over-fitting, it can specify the default direction of branch for missing number value or specified number value.…”
Section: (4) Extreme Gradient Boosting (Xgboost)mentioning
confidence: 99%